El aprendizaje de una profesión en la Universidad : Los maestros finiseculares - Joaquín Giró Miranda (Universidad de La Rioja, 2013)
This is a reflection on the socialization process in which the future teacher and educator of the new 21st century is plunged from the first year of his/her teacher training (with its different degrees) up to his/her graduation three years later. To identify this process of advanced socialization, we have selected as significant variables of its construction, development and transformation those that determine the expectations of his/her professional practice, as well as several aspects relevant in the interpersonal relations, which will be called attitudes and social values. The education system is aimed at its consolidation and preservation through the actions of its agents, mainly the teaching staff. These actions (fulfillment of administrative rules and education guidelines) are routinely and gradually adopted, that is to say, they are internalized by the teaching staff throughout a socialization process. Although this process lasts from the entry of an individual into a Teacher Training School up to his/her retirement, there is moment particularly special and deeply-rooted, i.e., the very beginning of the teacher training, where the individual is more receptive to the latest ideas and thus to the acceptance of the norms and values typical of the system he/she wants to gain access to through the socially approved procedure of the formal training in a Teacher Training School. It is the social acknowledgment of the teaching staff, and by extension, of the university diploma, that invites us to reflect on the socialization process that takes place at University during the three years of the degree. This process is understood as a combination of the acquisition of some knowledge and academic education and the acquisition of some ideas or models of the profession that will be used by the young graduates to cope with the labour market.